2021
DOI: 10.1038/s41419-021-04080-1
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA KCNQ1OT1 activated by c-Myc promotes cell proliferation via interacting with FUS to stabilize MAP3K1 in acute promyelocytic leukemia

Abstract: Uncontrolled proliferation is the hallmark of cancer cells. Previous studies mainly focused on the role of protein-coding genes in cancer cell proliferation. Emerging evidence showed that long non-coding RNAs (lncRNAs) also play critical roles in cancer cell proliferation and growth. LncRNA KCNQ1OT1 is found to contribute to carcinogenesis, but its role in acute promyelocytic leukemia (APL) is unclear. In this study, by analyzing data from Gene Expression Omnibus, The Cancer Genome Atlas database and our clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…According to the literature, lncRNA KCNQ1OT1 has also been proven to be involved in the progression of multiple diseases, such as osteolysis ( 47 ), fracture healing ( 48 ), myocardial ischemia/reperfusion injury ( 49 ), atrial fibrillation ( 50 ), and diabetic cardiomyopathy ( 51 ). Furthermore, research has shown that lncRNA KCNQ1OT1 is also related to the progression of acute promyelocytic leukemia ( 52 ), ovarian cancer ( 17 ), bladder cancer ( 53 ), and NSCLC ( 18 ). Moreover, studies demonstrated that lncRNA KCNQ1OT1 was involved in oxaliplatin-resistant colon cancer ( 16 ), methotrexate-resistant colorectal cancer ( 54 ), and cisplatin-resistant tongue cancer ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, lncRNA KCNQ1OT1 has also been proven to be involved in the progression of multiple diseases, such as osteolysis ( 47 ), fracture healing ( 48 ), myocardial ischemia/reperfusion injury ( 49 ), atrial fibrillation ( 50 ), and diabetic cardiomyopathy ( 51 ). Furthermore, research has shown that lncRNA KCNQ1OT1 is also related to the progression of acute promyelocytic leukemia ( 52 ), ovarian cancer ( 17 ), bladder cancer ( 53 ), and NSCLC ( 18 ). Moreover, studies demonstrated that lncRNA KCNQ1OT1 was involved in oxaliplatin-resistant colon cancer ( 16 ), methotrexate-resistant colorectal cancer ( 54 ), and cisplatin-resistant tongue cancer ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some of children who suffer from this disease, embryonal tumors also point to the role of KCNQ1OT1 in cancer development. [10] As a matter of fact, recent studies have identified increased KCNQ1OT1 expression in retinoblastoma, acute promyelocytic leukemia, [10] bladder, [11] ovarian, [12] and non-small cell lung cancer (NSCLC). [13] However, no study has investigated the expression of KCNQ1OT1 in thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, lncRNA KCNQ1OT1 contributes to the development of acute myeloid leukemia by interacting with FUS to enhance the stability of MAP3K1 mRNA. 11 Lin-28 homologue B (LIN28B) is an RBP, and aberrant high expression of LIN28B in LPS-exposed cardiomyocytes can accelerate septic cardiomyopathy development via increasing PDCD4 mRNA stability. 12 Interestingly, the StarBase database predicted that CDKN2B-AS1 could bind to LIN28B.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs can affect the stability of mRNAs via the interaction with RNA binding proteins (RBPs). For instance, lncRNA KCNQ1OT1 contributes to the development of acute myeloid leukemia by interacting with FUS to enhance the stability of MAP3K1 mRNA 11 . Lin‐28 homologue B (LIN28B) is an RBP, and aberrant high expression of LIN28B in LPS‐exposed cardiomyocytes can accelerate septic cardiomyopathy development via increasing PDCD4 mRNA stability 12 .…”
Section: Introductionmentioning
confidence: 99%